2015
DOI: 10.1016/j.commatsci.2015.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Cu precipitation at extended defects in bcc Fe: An atomistic study

Abstract: a b s t r a c tAs a starting point to understand Cu precipitation in RPV alloys, molecular dynamics and Metropolis Monte-Carlo simulations are carried out to study the effect of lattice defects on Cu precipitation by taking Fe-Cu system as a model alloy. Molecular dynamics simulations show that owing to the high heat of mixing and positive size mismatch, Cu is attracted by vacancy type defects such as vacancies and voids, and tensile stress fields. In accordance, preferential precipitation of Cu is observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Materials 2021, 14, x FOR PEER REVIEW 5 of 13 calculation results of binding energy in this paper are relatively consistent with the calculation results obtained by Zhang et al [11], which proves the correctness of the simulation parameters selected in this paper. It can be seen from the Table that in the 1 b nn and 2 b nn neighboring state, the binding energy of Cu-Cu and Cu-V is positive, indicating that Cu atoms and Cu atoms and vacancies are attracted to each other in this neighboring state.…”
Section: Calculation Of the Binding Energy Of Cu-cu And Cu-v And The Migration Energy Barrier Of Vacanciessupporting
confidence: 90%
See 1 more Smart Citation
“…Materials 2021, 14, x FOR PEER REVIEW 5 of 13 calculation results of binding energy in this paper are relatively consistent with the calculation results obtained by Zhang et al [11], which proves the correctness of the simulation parameters selected in this paper. It can be seen from the Table that in the 1 b nn and 2 b nn neighboring state, the binding energy of Cu-Cu and Cu-V is positive, indicating that Cu atoms and Cu atoms and vacancies are attracted to each other in this neighboring state.…”
Section: Calculation Of the Binding Energy Of Cu-cu And Cu-v And The Migration Energy Barrier Of Vacanciessupporting
confidence: 90%
“…The results indicate that vacancy can promote segregation of Cu atoms towards grain boundaries during aging. Zhang et al [ 11 ] calculated the binding energy between Cu atoms and vacancies, and between Cu atoms in BCC-Fe using MD. It was found that the binding energy between Cu atoms and vacancies is greater than that between Cu atoms, suggesting that when there are vacancies in the system, Cu atoms will preferentially bind to the vacancies, rather than binding to other Cu atoms, and vacancies may play the role of nucleation particles in the growth of the Cu precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…In reality heterogeneous precipitation of Cu at preexisting dislocations and irradiation induced defect clusters may also take place, affecting precipitation kinetics [33]. Such heterogeneous precipitation is thermodynamically preferred at various types of defects and has been demonstrated in an earlier work using Metropolis Monte Carlo [34]. This effect may be considered in the future by using cluster dynamics for both radiation damage and solute precipitation.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…Developed primarily for the microstructure evolution of Fe-Cu alloy under radiation, this potential is suitable for studying the phase transition of the Cu-rich precipitate 13 and interaction between Cu and lattice defects in bcc Fe. [34][35][36][37] The binding energy of Cu-Cu, Cu-vacancy, multiple Cu atoms with vacancy, and vacancy migration energy in pure Fe and Fe-Cu alloy was studied by MS simulations. Simulations were performed using a box of size 30×30×30 a 0 (where a 0 is the lattice constant of bcc Fe) along the [100], [010] and [001] directions.…”
Section: Simulation Methodsmentioning
confidence: 99%